The moderating effect of work experience on the relationship between accounting students’ big five personality characteristics, trait professional skepticism, and anticipatory socialization - Vani, Angela Mei; Santosa, Setyarini (JAAF (Journal of Applied Accounting and Finance), 2024)
Some studies in accounting categorized professional skepticism as trait professional skepticism and state professional skepticism. A prior study found that big five personality characteristics were correlated with trait professional skepticism and anticipatory socialization. State professional skepticism that is triggered by situational factor, might have an influence on the relationship. Therefore, this study examines the moderating effect of work experience, which represents the existence of state professional skepticism, on the relationship between big five personality characteristics and (1) trait professional skepticism; and (2) anticipatory socialization. The data were collected from 342 first to final-year undergraduate accounting students in several universities in Indonesia and then analyzed using regression analysis. The results show that work experience has no significant effect on the relationship between big five personality characteristics to trait professional skepticism and anticipatory socialization. However, this might be influenced by centralized distribution of questionnaire and the absence of separation between respondents who are currently working and no longer working.